PROCEDURE FOR MAKING CHANGES TO THE STAFF SCHEDULE IN INSTITUTIONS MID-YEAR - Ortiqov Khamarokul Abdumajidovich; Anvarova Guzal Khusan kizi (Labor economics and human capital, 2024)
This article discusses the current economic reforms aimed at further developing the economy, analyzing existing shortcomings and problems, and addressing them. It focuses particularly on improving the procedures for making changes to the staff schedule in professional educational institutions mid-year. The article highlights the implementation of the new UzASBO2 program as a result of ongoing reforms aimed at economic growth. It is emphasized that modern budget-funded organizations are utilizing contemporary electronic systems, which necessitates the adaptation of this program to current demands. Additionally, the creation of an electronic form of Appendix 15 has been developed for this purpose. The article provides a detailed overview of the process of its creation and approval.